2007
DOI: 10.1002/bmc.730
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and sensitive liquid chromatography–tandem mass spectrometry (LC‐MS/MS) method for the estimation of amlodipine in human plasma

Abstract: A rapid and sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method has been developed and validated for the estimation of amlodipine in human plasma. Amlodipine was extracted from human plasma by using a solid-phase extraction technique. Imipramine was used as the internal standard. A Hypersil BDS C18 column provided chromatographic separation of analytes followed by detection with mass spectrometry. The method involves a rapid solid-phase extraction from plasma, simple isocratic chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 12 publications
(9 reference statements)
1
48
1
Order By: Relevance
“…the recovery and stability studies were done using this method. The authors concluded that this method is rapid sensitive accurate and simple, therefore it can be used in determination of amlodipine in human plasma for pharmacokinetic and bioequivalence studies [35]. A new LC-MS-MS method for the simultaneous determination of amlodipine, losartan and losartic acid in human plasma was developed and validated by Karra and co-workers.…”
Section: 42mentioning
confidence: 99%
“…the recovery and stability studies were done using this method. The authors concluded that this method is rapid sensitive accurate and simple, therefore it can be used in determination of amlodipine in human plasma for pharmacokinetic and bioequivalence studies [35]. A new LC-MS-MS method for the simultaneous determination of amlodipine, losartan and losartic acid in human plasma was developed and validated by Karra and co-workers.…”
Section: 42mentioning
confidence: 99%
“…Amlodipine besylate is official in IP [2] and BP [3] and Hydrochlorthiazide is official in IP [2], BP [3] and USP [4]. Literature survey revealed that various methods such as UV [9,10,15,16,19,20], HPLC [11,17], HPTLC [12,18], LC-MS/MS [13] and UPLC [14] are available in single and combination with other drugs. However, no spectrophotometric method has yet been reported for simultaneous estimation of amlodipine besylate, olmesartan medoxomil and hydrochlorthiazide in tablet dosage forms.…”
Section: Amlodipine Besylate (Figure 1a) [1] Is 3-ethyl 5-methyl (4rsmentioning
confidence: 99%
“…Capillary electrophoresis methods were also used for the analysis of AML in its formulations and biological fluids [15,16]. AML was also determined using liquid chromatography mass spectrometry (LC-MS) [17,18]. 1, 2-naphthoquinone-4-sulphonate (NQS) has been used as a chromogenic reagent for the colorimetric determination of many pharmaceutical amines [19][20][21].…”
Section: Introductionmentioning
confidence: 99%